Agrophotovoltaic landscape an integration of solar-powered irrigation and land art in a rice farming community - Bernardo, Erylle Jane G. (College of Architecture, University of the Philippines Diliman, 2019)
The Philippines is the 8th largest rice producer in the world but it is excluded on the list of the world's top rice yielders due to its low average rice yield compared to other countries such as China, Vietnam and Indonesia. Due to rapid growth of population and industrialization in the Philippines, the amount of rice produced by agricultural lands in the country becomes insufficient, thus, importing rice from Thailand and Vietnam. Imagine how an agricultural country, which produces millions of tons of rice needs to import and sell rice at a very high rate. Although through the years, the Philippine's rice yield increases because of innovations on rice varieties and agricultural technologies, the increase still does not meet the demand of the growing population. Factors such as local conditions and land management. including irrigation and pet control affect rice yield. This thesis addresses the dilemma of irrigation insufficiency in Barangay Mangandingay, Science City of Munoz (SCM), Nueva Ecija. Barangay Mangandingay, with 1005 hectares of total land area only has one season for rice production which therefore causes lesser yield and income to the local farmers. The farmers rely on rainwater for irrigation due to their barangay's high elevation which is not reached by the government's irrigation infrastructure. Through an agrophotovoltaic (APV) landscape, an integration of solar-powered irrigation and rice paddy art, the study aims to address irrigation insufficiency while also strengthening cultural identity, economic security and environmental stability of the barangay.